The Nexus Between Government Revenue and Economic Growth in Nigeria - Joseph, Fineboy Ikechi; Omodero, Cordelia Onyinyechi (Economics and Business, 2020)
The aim of the study is to examine the relationship between government revenues and the economic growth of Nigeria. The study employs exploratory and ex-post facto research designs while using secondary form of data spanning from 1981 to 2018 collected from the Federal Inland Revenue Services (FIRS), National Bureau of Statistics and CBN statistical bulletin. The relationship is tested by using Ordinary Least Squares (OLS) regression technique. The result reveals that federally received revenue and Value Added Tax (VAT) have a moderate positive relationship with the economic growth. The study provides evidence that there is a need for the government to formulate relevant revenue policies that will boost government income in order to have more favourable implication on the economy.